Pemantauan Lingkungan pada Tahap Konstruksi Pekerjaan Preservasi Jalan Nasional di Provinsi Jambi - Brama Nalendra; Endi Adriansyah; Badariah Badariah; Saldi Yulistian; Shinta Oktaviana; Syahidullah Habibie; Randy Rizal; Esy Solvera (Jurnal Civronlit Unbari, 2026)
The increasing intensity of national road management activities in Jambi Province poses potential impacts on environmental quality in the surrounding areas. This study aims to conduct integrated multi-parameter environmental monitoring during the construction phase of the Bangko – Sungai Manau – Batas Kerinci – Sanggaran Agung Road Preservation Project in Jambi Province. A quantitative descriptive method was employed, with sampling conducted at three representative locations: the Contractor Basecamp/AMP (Location 1), Batang Merangin River at STA 0+250 (Location 2), and STA 35+025 (Location 3). Testing parameters included surface water quality (18 physical and chemical parameters), ambient air quality (5 parameters), odor (2 parameters), noise, and vibration. All assessments were conducted in accordance with Government Regulation No. 22 of 2021, Minister of Environment Decree No. 50 of 1996, and Minister of Environment Decree No. 49 of 1996. The results indicated that nearly all parameters remained below the prescribed quality standards. However, the Chemical Oxygen Demand (COD) value at Location 2 was recorded at 28.48 mg/L, exceeding the Class II standard of 25 mg/L, suggesting an influence of construction runoff on the water quality of Batang Merangin River. The highest values for air quality, noise, and vibration parameters were consistently found at Location 1, attributed to the operation of heavy mechanical equipment. Compared to similar studies on urban road construction and toll road projects, this study demonstrates lower environmental impacts; however, consistent environmental management in accordance with applicable regulations remains necessary.